(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
The integration of the Iberian Peninsula into the Roman world favoured the participation of Hispanics in the army. Although the majority did so in the legionary and auxiliary troops, a minority met the demanding requirements for service in the urban militia of Rome, made up, among other bodies, of the Praetorian Guard, the urban cohorts, the corps of vigiles and the equites singulares Augusti. In this work we have set out to compile, update and study the literary and epigraphic references relating to the Hispanics who served in these units, thus offering an overview of their role in the urban militia of Rome. In our analysis we will address aspects such as the places of origin of the characters studied, their legal status, their onomastics, their social relations or the activity they carried out in their respective units.